Reducing Re-Absorption Losses In Luminescent Solar Concentrators ( LSC’s) By Using Nanomaterials - Mohd Nazree, Muhammad Azlan Nasrin (IRC, 2016)
Harvesting optical energy from the sun has been an alternative since many years ago, with the use of conventional solar photovoltaic cells, collecting light energy from the sun to be converted into electrical energy for conventional use. The advances in technology forces the solar energy pioneers to further research and study the advances that can be made to the solar panels, and thus, resulting in the invention of Luminescent solar concentrators. Despite having saved loads of cost and its better effectiveness, this solar concentrator has somehow failed to cope with the optical losses that can occur whether inside or out of the concentrator, when using organic dyes as the luminophores. Thus a more effective method is suggested by some researchers, leading to the use of quantum-dot nanocrystals as luminophores to be dispersed inside the concentrator. The use of quantum dots has been proven effective, as shown in past studies stated in this paper. This paper has the objective to further reduce the optical losses in terms of self-absorption by developing new quantum dots As for a mathematical model, the equation used is the Brus Equation.